Improving administrative procedures and organizational principles of professional training of police officers in Ukraine - A. V. Potopalskyi (Law and Safety)
In the article, on the basis of analysis of norms of the current legislation of Ukraine and scientific views of scientists, ways of improving administrative procedures and organizational principles of professional training of police officers in Ukraine are worked out.